2019
DOI: 10.1111/1462-2920.14618
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between zinc and iron homeostasis in Aspergillus fumigatus under zinc‐replete conditions relies on the iron‐mediated regulation of alternative transcription units of zafA and the basal amount of the ZafA zinc‐responsiveness transcription factor

Abstract: Summary Aspergillus fumigatus is a saprophyte fungus that typically grows on organic decaying matter but can also parasitize immunosuppressed hosts. This is explained, in part, by its great ability to take up Zn2+ ions from living tissues, which is induced by the ZafA transcription factor. This study shows that the ZafA‐mediated regulation of fungal growth is also influenced by iron availability and that A. fumigatus is well adapted to grow in zinc‐limiting and zinc‐replete media with Zn:Fe ratios lower in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Additionally, A. fumigatus growth in zinc-replete conditions relies on iron availability. The expression of different transcription subunits of ZafA is controlled by iron levels, culminating in basal amounts of this transcription factor that regulate optimal fungal growth in zinc-replete conditions [76]. Those examples highlight the complexity and tight regulation of zinc homeostasis performed by A. fumigatus in response to pH, zinc and iron levels, as well as the interplay between transition metals metabolism.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, A. fumigatus growth in zinc-replete conditions relies on iron availability. The expression of different transcription subunits of ZafA is controlled by iron levels, culminating in basal amounts of this transcription factor that regulate optimal fungal growth in zinc-replete conditions [76]. Those examples highlight the complexity and tight regulation of zinc homeostasis performed by A. fumigatus in response to pH, zinc and iron levels, as well as the interplay between transition metals metabolism.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…C. dubliniensis in counterpart, is considered less pathogenic [80] and is mainly associated with HIV-infected patients [81]. A recent study has shown that the transition metal iron as well as a transcription factor related to copper tolerance also influence zinc homeostasis in A. fumigatus [76,77]. Cai and co-workers demonstrated that Ace1, previously described as a copper detoxifying transcriptional regulator, is also essential for adaptation to high zinc levels.…”
Section: Candida Albicans and Candida Dubliniensismentioning
confidence: 99%
“…As noted above, the MetR transcription factor specifically induces genes required for sulfate assimilation in A. fumigatus (Amich et al, 2013), whereas the mitochondrial cysteine synthase CysB catalyzes the incorporation of S 2− coming from sulfate reduction into O-acetylserine to generate Cys (Brzywczy et al, 2007). Currently, it is unclear whether metR and cysB repression is exerted directly or indirectly by ZafA, which is the major transcriptional regulator of zinc homeostasis in A. fumigatus (Vicentefranqueira et al, 2018(Vicentefranqueira et al, , 2019, although the presence of two ZR-like motifs (i.e., Zinc Response consensus motifs) at 2000 and 1272 bp upstream the translation start codon (TSC) of metR and a ZR-like motif at 318 bp upstream the TSC of cysB indicates that a direct ZafA-mediated repression of these genes is possible. In either case, the lower expression of metR and cysB under zinc-limiting rather than under zincreplete conditions suggest that zinc starvation might reduce sulfate assimilation and mitochondrial Cys biosynthesis in A. fumigatus.…”
Section: Regulation Of Sulfur Metabolites By Zinc Starvationmentioning
confidence: 99%
“…Essential nutrients include minerals such as iron, copper, and zinc, which are required in small amounts, while carbon and nitrogen, the main energy sources for sustaining biosynthetic processes, must be obtained in large quantities ( 3 ). Iron, zinc, and copper acquisition and metabolism have been studied in A. fumigatus in the context of virulence ( 4 6 ), whereas less is known about carbon source acquisition and metabolism in this fungus during infection. Studies have inferred that glucose, lactate, and acetate are carbon sources available to fungi in vivo with their availability and concentration depending on the host niche ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%